MSC-based therapy in female pelvic floor disorders - Sima, Yizhen (Cell Biosci, 2020)
Mesenchymal stem cells (MSCs), also referred to as multipotent stromal cells or mesenchymal stromal cells, are present in multiple tissues and capable of differentiating into diverse cell lineages, holding a great promise in developing cell-based therapy for a wide range of conditions. Pelvic floor disorders (PFDs) is a common degenerative disease in women and may diminish a woman’s quality of life at any age. Since the treatments for this disease are limited by the high rates of recurrence and surgical complications, seeking an ideal therapy in the restoration of pelvic floor function is an urgent issue at present. Herein, we summarize the cell sources of MSCs used for PFDs and discuss the potential mechanisms of MSCs in treating PFDs. Specifically, we also provide a comprehensive review of current preclinical and clinical trials dedicated to investigating MSC-based therapy for PFDs. The novel therapy has presented promising therapeutic effects which include relieving the symptoms of urinary or fecal incontinence, improving the biological properties of implanted meshes and promoting the injured tissue repair. Nevertheless, MSC-based therapies for PFDs are still experimental and the unstated issues on their safety and efficacy should be carefully addressed before their clinical applications.